2017
DOI: 10.1088/1742-6596/896/1/012125
|View full text |Cite
|
Sign up to set email alerts
|

On modelling of shear fracture in deep drawing of a high-strength dual-phase sheet steel

Abstract: A new specimen for out-of-plane shear strength of advanced high strength steel sheets B Gu, J He, S H Li et al. Abstract. The paper presents application of fracture behaviour characterisation results of a dual-phase sheet steel DP600 to an FEA of its deep-drawing for shear fracture prediction. The characterisation results were obtained with the help of a characterisation method based on a tensile test on a novel butterfly specimen and published previously by the authors. The aim of the present paper is to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In a comprehensive study, Behrens et al compared different experimental methods and discussed the advantages and disadvantages of common tests [7]. In this study and in a further application in [2], a methodology with a special butterfly specimen geometry, which was developed at the IFUM [8], showed good applicability for a DP600 steel. This approach is therefore chosen to be applied in this work for the investigation of the damage behaviour of two other AHSS, a dual-phase DP1000 and a complex-phase CP800 sheet metal material.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In a comprehensive study, Behrens et al compared different experimental methods and discussed the advantages and disadvantages of common tests [7]. In this study and in a further application in [2], a methodology with a special butterfly specimen geometry, which was developed at the IFUM [8], showed good applicability for a DP600 steel. This approach is therefore chosen to be applied in this work for the investigation of the damage behaviour of two other AHSS, a dual-phase DP1000 and a complex-phase CP800 sheet metal material.…”
Section: Introductionmentioning
confidence: 85%
“…This results in a propensity for different crack appearances, without prior indication by thinning, like exemplary shear fracture on tight radii and edge-fracture, which all can not be predicted by an FLC. These challenges in numerical damage prediction are exemplary demonstrated in [1] and confirmed in [2]. Moreover, the fracture behaviour of AHSS compared to conventional steels, results in a propensity for shear failure as opposed to ductile failure caused by thinning for example during automotive panel stamping.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the results indicated that the MMC model outperformed the FLC criterion in dealing with NLSPs and shear-induced fracture. Nevertheless, Behrens et al [236] highlighted the significance of considering no damage accumulation effects for stress triaxialities below −0.33 in the MMC formulation. Their study detected premature shear fracture initiation of a DP600 steel workpiece in a deep drawing operation without the aforementioned condition.…”
Section: Modified Mohr-coulomb Model (Mmc)mentioning
confidence: 99%